Characterization of Escherichia coli isolated from carcasses of beef cattle during their processing at an abattoir in Brazil - Rigobelo, E. C.; Stella, A. E.; Avila, F. A.; Macedo, C.; Marin, J. M. (Elsevier B.V., 2006)
Beef carcass sponge samples collected between March 2003 and August 2005 at an abattoir in Brazil were surveyed for the presence of Shiga toxin-producing Escherichia coli (STEC). Only one carcass among the 80 tested showed a STEC, stx2-encoding gene by PCR amplification. The frequency of carcass contamination by E. coli during processing was tested at three situations, respectively: preevisceration, postevisceration and postprocessing, during the rain and dry seasons. The prevalence of E. coli at the three points was of 30.0%, 70.0%, 27.5% in the rain season and of 22.5%, 55.0%, 17.5% during the dry season, respectively. The E. coli isolates exhibited a high level (45.0%) of multidrug resistance to two or more antimicrobial agents. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Escherichia coli; beef carcass; STEC; abattoir; multidrug resistance